Avaliação da capacidade de remoção de corante têxtil pelo fungo Lasiodiplodia theobromae MMPI em efluente sintético e industrial - Pizato, Everton (2013)
The industrial processes of textile production are characterized by the use of large volumes of water during the steps of washing and dyeing fabric, resulting in effluent with enormous diversity and chemical complexity. The presence of dye dissolved in the effluent is quite noticeable and problematic, considering its recalcitrance and slow degradation kinetics. In this work, the fungus ascomiceto L. theobromae MMPI were evaluated for the ability to color removal from synthetic effluent containing blue dye reactive and industrial effluent. The tests with synthetic effluent were performed in incubator orbital shaker and in bioreactor with tub of 5L. The media was supplemented with MgSO4.7H2O 2 g L-1, K2HPO4 2 g L-1, autoclaved (121 C/15 min), plus sucrose, ammonium nitrate and stirring speed according to central composite design (CCDR), temperature 28 C, inoculum standardized and time to withdrawal of samples 72h. The color removal efficiency ranged from 31.58% to 91.60% and the biomass yield 0.40 g L-1 to 8.70 g L-1. It was still observed the production of an exopolysaccharide (EPS) in the range of 0.66 g L-1 to 9.70 g L-1. In the analysis of estimated effects (p <0.05) only the linear effect of sucrose concentration (p <0.000) and quadratic effect of the concentration of ammonium nitrate (p <0.018) were significant. The model was evaluated by ANOVA, with high regression coefficient considering a biological system (R2 0.8483). This model was validated by experiment retrospectively, indicating excellent correlation between the predictive value (74.8%) and the observed value (73.8%). The tests in bioreactor ratified the behavior observed in an incubator shaker to give 86% decolorization of synthetic effluent at the end of 72 hours of treatment of discoloration and 91.3% at the end of 168 hours of treatment for industrial effluent. After 168 h of incubation was observed laccase enzyme activity (0.0563 U / ml). The acute toxicity tests with brine shrimp showed that the LC50 was approximately 14.72% (v / v) for the raw wastewater, while the effluent subjected to the treatment eight days was approximately 4.98% (v / v). Several authors relate the processes of bleaching enzyme activity, however the results suggest that the color removal is related to the adsorption of the dye in the biomass produced. Further studies should be performed for better understanding and confirmation that the color removal is not associated with the biosynthesis of phenolic structures degrading enzymes such as laccases.